2017
DOI: 10.3390/vaccines5040033
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Burkholderia cenocepacia TonB Mutant as a Potential Live Attenuated Vaccine

Abstract: Burkholderia cenocepacia is an opportunistic pathogen prevalent in cystic fibrosis patients, which is particularly difficult to treat, causing chronic and eventually fatal infections. The lack of effective treatment options makes evident the need to develop alternative therapeutic or prophylactic approaches. Vaccines, and live attenuated vaccines, are an unexplored avenue to treat B. cenocepacia infections. Here we constructed and characterized a B. cenocepacia tonB mutant strain, which was unable to actively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…However, further study of the essential genomes of other species of the genus Burkholderia is needed to confirm this hypothesis. Efforts are ongoing to find alternatives to conventional treatments for pathogenic species of the genus Burkholderia [ 103–106 ]. The envelope proteins identified in this work may represent ideal candidates for immunogenic targeting, as conserved essential proteins are less prone to variability.…”
Section: Discussionmentioning
confidence: 99%
“…However, further study of the essential genomes of other species of the genus Burkholderia is needed to confirm this hypothesis. Efforts are ongoing to find alternatives to conventional treatments for pathogenic species of the genus Burkholderia [ 103–106 ]. The envelope proteins identified in this work may represent ideal candidates for immunogenic targeting, as conserved essential proteins are less prone to variability.…”
Section: Discussionmentioning
confidence: 99%
“…As to TonB3 druggability, it is important to underline that tonB3 is among the genes whose expression is upregulated during bacteremia (56) and that no homologs of TonB3 have so far been identified in mammals, hopefully limiting toxicity issues related to the administration of TonB3 inhibitors. Moreover, some studies indicate that avirulent tonB mutants represent suitable backbone strains for future vaccine development against Klebsiella pneumoniae, Burkholderia mallei, and Burkholderia cenocepacia infections (51,57,58). Given the increasing antibiotic resistances of A. baumannii and the essentiality of iron for A. baumannii growth in vivo, the data presented in this study highlight TonB3 as a suitable target for the development of new antimicrobial compounds and pave the way to testing tonB3 mutants as attenuated A. baumannii vaccines.…”
Section: Discussionmentioning
confidence: 82%
“…The uptake of ferric siderophore complexes by Burkholderia species require different outer membrane receptors that interact with an inner membrane TonB complex (TonB, ExbB, and ExbD) (17, 18). Previously, our group demonstrated that disruption of tonB reduces the virulence of Burkholderia mallei and Burkholderia cenocepacia both in vitro and in vivo (19, 20).…”
Section: Introductionmentioning
confidence: 99%